The experience of social dialogue in Poland - Barańska, Bogumiła (Univerzita Pardubice, 2010)
Social dialogue, according to the European Union, is a process of constant interaction between social partners aiming to reach agreement on executing control over certain economic and social variables, both on a macro- and microeconomic level, to put it in simpler terms, social dialogue is the exchange of information and the presentation of opinions on social issues and problems. The sides of social dialogue are the trade unions side, representing the interests of employees who are members of organizations operating on all levels of social dialogue, the employers side, representing the interests of employers who are members of organizations operating on all levels of social dialogue, and the government’s side, representing the interests of the state and consisting of the representatives of the executive branch. The partners are the units of self-government, industry self-governing councils, other social organizations and the representatives of professional and artistic circles. The aim of all partners from social circles, politicians and officials participating in the dialogue is social partnership and institutionalized social dialogue is necessary, despite serious criticism of the current dialogue in Poland.
Keywords: social dialogue; dispute; conflict; determinants of social dialogue; social consultation; public administration; government